Studi Analisis Hubungan Iklim Mikro Terhadap Kondisi Kenyamanan Termal Ruang Kuliah Jurusan Geografi FMIPA Universitas Negeri Makassar - Nasrul; Dita Eka Nur; Rini Kausarani; Misdar Amdah; Arfandi; Rahma Musyawarah; Medar M Nur; Aulia Diar Hasja; Rosmini Maru (PT. Lontara Digitech Indonesia, 2024)
Indoor learning and teaching activities definitely require comfort so that the activities run well, calmly and comfortably. The aim of this research is to determine changes in room temperature over time in the Geography Department, FMIPA, Makassar State University. This research was conducted in FI 106, FI 107 and PPG rooms. The type of research used is descriptive research by processing data from field measurements to see the thermal comfort conditions in the Geography Department lecture hall, Makassar State University. The results showed that the room temperature changed over time. The room temperature from 08.00 to 14.00 has a significant temperature difference. The highest average measurement was in the PPG room, namely 30℃, while the lowest average temperature was in the FI 106 room, namely 29.5. The three rooms have an average temperature above the optimal comfort scale, namely 29.7℃. The lowest average temperature was obtained at 08.00 and the highest average temperature at 14.00 reached 32.2℃. This research has implications for efforts to handle thermal comfort problems in study rooms as a support for learning activities on the Geography Department campus, Faculty of Mathematics and Natural Sciences, Makassar State University